Le Fort III fracture with fronto basal fistula closure. Case report - Santillan Orozco, Christian Ricardo (2023)
The management of panfacial and midfacial trauma requires not only knowledge of basic osteosynthesis principles and techniques, but also a methodical protocol of action before surgery and adapted to each patient. The present case is about a male patient in the second decade of life with panfacial traumatism after a traffic accident with direct impact who came to the Pablo Arturo Suarez Hospital in the city of Quito as an emergency patient. On initial evaluation, he presented Glasgow scale 10/15 and reported swallowing salty liquid on verbal response, significant edema in the face, bilateral periorbital ecchymosis, bilateral subconjunctival hemorrhage, friction abrasions in nasal and genital region, blood stigmata in nostrils and mouth, significant edema in upper and lower lip, step at premaxilla level on the right side, loss of continuity of occlusion, limited mouth opening. Her diagnosis was Le Fort class III fracture, with frontobasal fistula with retropharyngeal flow of cerebrospinal fluid. The aim of this report is to describe the multidisciplinary surgical sequence in coordination with neurosurgery and the postoperative management of panfacial trauma and complex fractures of the middle third.